Гарантії забезпечення трудових прав запозичених працівників - Гусаров, О. С.; Husarov, O. S. (Держава та регіони. Серія: Право. – 2020. – № 3(69), т. 3. – С. 22-27, 2020)
Виділено та охарактеризовано гарантії забезпечення трудових прав запозичених працівників. Гарантії-принципи, являють собою сукупність інструментів та засобів, які спрямовані на створення політичних, економічних та правових умов для розвитку інституту запозиченої праці взагалі, а також забезпечення та захисту праці досліджуваною категорією працівників, зокрема. Окрім того, саме вказані гарантії спрямовані на те, щоб працівники могли вільно реалізувати право на працю, а також відновити їх порушені права. Зроблено висновок, що на сьогоднішній день, питання гарантій забезпечення трудових прав працівників, що здійснюють трудову діяльність на умовах запозиченої праці, досить поверхнево врегульовано нормами чинного законодавства.

Today, borrowed labor has a number of advantages that determine its attractiveness for the user enterprise: first of all, it saves money on the salary fund, saves time on the processes of recruiting personnel with the necessary qualifications, transfers responsibility for the timeliness and correctness of transfers to social funds to a private employment service. The purpose of the article is to describe the guarantees of ensuring the labor rights of borrowed employees. In the article, based on the analysis of the scientific views of scientists and the norms of the current legislation, the guarantees of ensuring the labor rights of borrowed employees are highlighted and characterized. Guarantees-principles represent a set of tools and means aimed at creating political, economic and legal conditions for the development of the institution of borrowed labor in general, as well as ensuring and protecting the work of the studied category of workers, in particular. In addition, these guarantees are aimed at ensuring that workers can freely exercise their right to work, as well as restore their violated rights. It was concluded that today, the issue of guaranteeing the labor rights of employees performing labor activities under the conditions of borrowed labor is rather superficially regulated by the norms of the current legislation. This is due to the fact that the legislator actually equates borrowed employees with general categories of employees. This undoubtedly leads to: firstly, violation of the rights, freedoms and interests of the investigated employees; secondly, it reduces opportunities for using the appropriate form of employment and involving citizens in it, which in turn contradicts the leading world practice. In view of the above, we are convinced that an important task of the legislator and domestic scientists is the implementation of active activities in the direction of expanding the scope and content of guarantees for ensuring the labor rights of temporary workers, and therefore their further consolidation in the Labor Code of Ukraine, the adoption of which should be an important step in the direction of the development of atypical forms of employment in general and borrowed labor, in particular.

Выделены и охарактеризованы гарантии обеспечения трудовых прав заимствованных работников. Гарантии-принципы представляют собой совокупность инструментов и средств, направленных на создание политических, экономических и правовых условий для развития института заемного труда вообще, а также обеспечения и защиты труда исследуемой категорией работников, в т. ч. Кроме того, именно эти гарантии направлены на то, чтобы работники могли свободно реализовать право на труд, а также восстановить их нарушенные права.
The guarantees of ensuring the labor rights of borrowed employees
Keywords: запозичена праця; трудові права; гарантії; працівники; нетипові форми зайнятості; borrowed labor; labor rights; guarantees; workers; atypical forms of employment; заимствованная работа; трудовые права; гарантии; работники; нетипичные формы занятости